Integrated mission reliability modeling based on extended quality state task network for intelligent multistate manufacturing systems. (July 2022) - Yang, Xiuzhen; He, Yihai; Liao, Ruoyu; Cai, Yuqi; Ai, Jun
Highlights: Operational quality evolution mechanism of intelligent multistate manufacturing systems is expounded. EQSTN is established to characterize the functional fitness quality of manufacturing system. Integrated mission reliability model based on EQSTN is presented. An industrial example of an intelligent multistate manufacturing system is implemented. Abstract: The quality of produced WIP(work-in-process) is the direct indicator of operational reliability of manufacturing system. To assure the predictability of the reliability of finished products is the paramount goal for the operation and maintenance of intelligent manufacturing systems. Therefore, a novel integrated mission reliability modeling approach based on extended quality state task network (EQSTN) for intelligent multistate manufacturing systems is proposed in this paper. First, to guarantee the reliability of final produced products, the relationship between the manufacturing system reliability and the produced product reliability is explained from the systematic perspective. The connotation of integrated mission reliability of intelligent multistate manufacturing systems is also provided. Second, an EQSTN is proposed based on operational quality data by extending the traditional dimensional conformance quality to functional fitness quality. Third, based on the established EQSTN, an integrated mission reliability modeling approach is proposed to quantitate the operational healthy state of the intelligent manufacturing system dynamically. Finally, a case study of an intelligent multistate manufacturing system for a ball screw pair is conducted to verify the proposed approach.